2014
DOI: 10.1590/1678-4499.0153
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento de grãos e características agronômicas de soja em função de pastagens perenes em sistema de plantio direto

Abstract: ResumoO objetivo do presente estudo foi avaliar o desempenho de soja em sistemas de produção com integração lavoura-pecuária em plantio direto. Constituíram os tratamentos cinco sistemas de produção: sistema I (trigo/soja, ervilhaca/milho e aveia branca/soja); sistema II (trigo/soja, pastagem de aveia preta + ervilhaca/milho e aveia branca/soja); sistema III (pastagens perenes da estação fria: festuca + trevo branco + trevo vermelho + cornichão); sistema IV (pastagens perenes da estação quente: pensacola + ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
2
9
0
2
Order By: Relevance
“…Forage intercropped with soybean did not affected soybean yield. These results corroborate with Santos et al (2013) and Silva et al (2015), which evaluated soybean intercropped with forages in integrated crop-livestock, also did not observed differences between treatments for agronomic characteristics; however, the results were different those found by Bahry et al (2013), were a significant difference was only found for plant height. In several studies where advantages of forages as cover crops are shown, a strong relationship with soil attributes mostly in the soil chemistry, soil physics and some crop health were demonstrated to be improved by cover crop adoption (Pariz et al, 2014;Franzluebbers et al, 2014).…”
Section: Resultssupporting
confidence: 90%
“…Forage intercropped with soybean did not affected soybean yield. These results corroborate with Santos et al (2013) and Silva et al (2015), which evaluated soybean intercropped with forages in integrated crop-livestock, also did not observed differences between treatments for agronomic characteristics; however, the results were different those found by Bahry et al (2013), were a significant difference was only found for plant height. In several studies where advantages of forages as cover crops are shown, a strong relationship with soil attributes mostly in the soil chemistry, soil physics and some crop health were demonstrated to be improved by cover crop adoption (Pariz et al, 2014;Franzluebbers et al, 2014).…”
Section: Resultssupporting
confidence: 90%
“…The same occurred in comparison to sowing period where forage systems did not influence the plant heights. The effect of vegetation on the agronomic characteristics of soybean were also evaluated in some studies as the Santos et al (2014b) found that soybean plants heights ranging from 85 to 90 cm in different covers of perennial pastures under no-tillage system, being similar to those obtained in this study.…”
Section: Agronomic Characteristics and Yield Of Soybeansupporting
confidence: 81%
“…As for the weight of 100 grains, there was no significant effect (P>0.05) for forage systems and sowing period (Table 6). Many studies also found no effect of different vegetation cover on the weight of 100 seeds, as shown in the research of Lima et al (2009);Santos et al (2014b) and Borges et al (2015). The results obtained for grain yield were influenced (P<0.05) by forage systems and sowing period (Table 6).…”
Section: Agronomic Characteristics and Yield Of Soybeanmentioning
confidence: 86%
“…These results were probably because the genetic similarity between the genotypes, since most of them have common parents (Table 1). Moreover, bean yield is a polygenic quantitative characteristic, and thus highly affected by the environment (SANTOS et al, 2014).…”
Section: Resultsmentioning
confidence: 99%